1971
DOI: 10.1115/1.3408895
|View full text |Cite
|
Sign up to set email alerts
|

Discussion: “Indentation of a Circular Membrane” (Yang, W. H., and Hsu, K.-H., 1971, ASME J. Appl. Mech., 38, pp. 227–230)

Abstract: pressures near the slot are again observed and the explanation no doubt lies in the flow curvature in the entrained flow, which is greater for the larger values of t/y c . The effect was first reported by George [4].The law-of-the-wall for wall jets is established in the present paper. The same conclusion is reached by Guitton, [5], for wall jets over logarithmic spirals when the curvature is small. This, and other work, is mentioned in the review paper by Newman [6].The inaccuracy of the von Karman momentum e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Force F 1 would be acting on the interface between the incident bar and the specimen whereas force F 2 would be acting on the interface between the transmitter bar and the specimen. The specimen geometry and L/D ratio are important to achieve dynamic stress equilibrium within the specimen [6][7][8][9]. The studies presented are with metallic materials considering elastic wave propagation [8].…”
Section: Plain Weave E-glass/epoxymentioning
confidence: 99%
See 2 more Smart Citations
“…Force F 1 would be acting on the interface between the incident bar and the specimen whereas force F 2 would be acting on the interface between the transmitter bar and the specimen. The specimen geometry and L/D ratio are important to achieve dynamic stress equilibrium within the specimen [6][7][8][9]. The studies presented are with metallic materials considering elastic wave propagation [8].…”
Section: Plain Weave E-glass/epoxymentioning
confidence: 99%
“…After Kolsky [5] introduced the split bar technique for dynamic testing of specimens, SHPB has become the widely used experimental technique to test the materials at high strain rates. Various studies were carried out on specimen design [6], stress uniformity [7] and stress wave reverberation [8,9]. It was observed that the loading pulse with larger rise time generates better stress uniformity than the loading pulse with lesser rise time [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation